Implications of Knowledge Management in Vocational Education - Rismita Rismita; Bunyamin Bunyamin (Universitas Negeri Makassar, 2022)
This study analyzes the differences between the levels of management knowledge possessed by vocational high school teachers. The problem in this research is the shortage of vocational teachers who teach productive subjects, so that there is a gap in the skills possessed by graduates. This study uses a quantitative approach with Chi-Squared analysis, data collection is done by distributing online questionnaires and documents. The sample amounted to 62 respondents using a non-probability sampling technique, namely saturated sampling. The results showed that there was no significant difference between knowledge management and the category of teachers (vocational and non-vocational). These results mean that every teacher who teaches at Muhammadiyah vocational schools has the same knowledge competence in designing, organizing, carrying out tasks, and controlling school programs.